Формы и источники финансирования инноваций (Путеводитель предпринимателя, 2020)
In given article forms and sources of financing of innovations reveal, and also the information on efficient control innovative activity is resulted. Questions of calculation of means necessary for realisation of the investment project and carrying out of the analysis of possible sources of financing are considered.